Finite-time blow-up and global convergence of solutions to a nonlocal parabolic equation with conserved spatial integral. (April 2018) - Wang, Heng-Ling; Tao, Wei-Run; Wang, Xiao-Liu
Abstract: In this note we investigate the evolution behaviour of the solutions to a nonlocal parabolic equation with conserved spatial integral. For the non-global solutions, the blow-up rate for L p norm of the solutions is estimated from below. For several classes of initial data, the convergence of the global solutions is established.